Online reservation express bus ticket system VIS interactive map - Goh, Soon Kheak; Heah, Kooi Huang; Ong, Mee Mee (University Malaysia Sarawak (UNIMAS), 2002)
During today's age of information, implementation of calendar system in the web is very general. This implementation also known as online calendar system, which is more interactive and attractive than manual planner or organizer. Online calendar system helps a user or community to organize their daily life more effective and efficient.